The Characterization Methods of Natural Fibers (Cellulose Fibers) as Reinforcement for Polymer Matrix Composites: A Review : Natural Fibers Characterization - Perima, Yoan; Iman Mainil, Rahmat (Mechanical Engineering Department - Semarang State Polytechnic, 2025)
The interest in using natural fibers as reinforcement in polymer matrix composites is increasing, driven by their abundant availability, biodegradability, and significantly lower production costs compared to synthetic fibers. The cellulose content in natural fibers has a significant impact on the mechanical properties and thermal stability of the fibers, ultimately affecting the mechanical strength of the composites. To enhance the cellulose content in the fibers, one approach is to use alkali treatment with a NaOH solution on the fibers. To evaluate the effectiveness of the chemical treatment and study the physical and mechanical characteristics of the fibers, as well as to assess the potential and feasibility of the fibers as reinforcement in polymer matrix composites, a series of characterizations or tests on the fibers needs to be conducted. This review article will discuss in depth the methods of characterizing natural fibers and the influence of their physical and mechanical properties on composite strength. This article is expected to provide a positive contribution to the development of polymer matrix composite materials reinforced with natural fibers.